2013
DOI: 10.1088/0963-0252/22/5/055008
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic sterilization effect of microwave-excited nonthermal Ar plasma, H2O2, H2O and TiO2, and a global modeling of the interactions

Abstract: A microwave-excited atmospheric-pressure plasma jet (uAPPJ) exhibited a synergistic sterilization effect when combined with hydrogen peroxide (H 2 O 2 ), distilled water (DW) and titanium dioxide (TiO 2 ) photocatalysis. The sterilization efficacy of H 2 O 2 -uAPPJ increased as the H 2 O 2 concentration increased. The addition of TiO 2 also remarkably increased the sterilization efficacy. To find the main factor for the sterilization effect, optical emission spectra and the degradation rate of a methylene blue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 38 publications
3
31
0
Order By: Relevance
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 92%
See 2 more Smart Citations
“…Thence, the bulk plasma density n bulk can be calculated 8:3 Â 10 20 m -3 approximately. It should be mentioned that although this density value is consistent with previous studies reported from the similar lowerpower argon microwave plasma jets driven by continues microwave power in ambient air, [3][4][5][6][7][8][9][10][11][12][13][14][15][16]32 the actual plasma density of the pulsed plasma jet is lower than this value, due to the average power absorbed by the electrons lower largely in pulsed discharge with the same peak power amplitude.…”
Section: Experimental Summarysupporting
confidence: 92%
“…(18) and the operation of plasma fluid subloop (Eqs. (6) and (7)) starts. After 992 iterations, the converged solution of the electron density and electron temperature is arrived at.…”
Section: Methods For Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Non‐equilibrium atmospheric pressure plasma jets (APPJs) have been attractive for many biomedical applications, ranging from cancer cell treatment, sterilization, wound healing, coagulation, and tooth whitening . Compared with the low‐pressure plasmas, APPJs have advantages because they can be operated without a bulky vacuum pump with relatively low power requirements .…”
Section: Introductionmentioning
confidence: 99%
“…The increment rate (≈3.9 µM/min) was more than twice larger than that (≈1.5 µM/min) of UV/TiO 2 [11] with smaller amount of powder. It is considered the synergistic effect of plasma and TiO 2 , as observed in the research of plasma sterilization [12]. Plasma also can activate the TiO 2 and the electric field can help the separation process of photo-generated carriers to enhance the catalytic effect [13].…”
Section: Synergistic Effect Of Plasma and Tiomentioning
confidence: 99%